2021
DOI: 10.1016/j.healthpol.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Apps as a Digital Intervention Policy: A Longitudinal Panel Data Analysis in South Korea

Abstract: Many countries have developed COVID-19 tracking apps that help individuals trace and detect “people” who are likely to have come in contact with confirmed patients. However, their adoption rates remain low. This study, therefore, investigated South Koreans’ adoption and usage behaviors of COVID-19 apps that detect the “place” where infectious people are found and alert people within 100m in dangerous zones. Our focus was on such apps’ impact on various facets of human life . Specifically, we analyzed mobile ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Thirdly, the verification process also poses technical challenges to the developers of COVID-19 vaccination verification systems and apps. While some countries, such as South Korea, employed the latest technical solutions such as blockchain technology in the verification of the COVID-19 vaccination certificates, many other countries were not doing so or were not able to do so, though the potential in the application of emerging technologies, such as blockchain technology, has been mentioned as a way forward to protect personal privacy implemented in COVID-19 vaccine passports and contact tracing [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the verification process also poses technical challenges to the developers of COVID-19 vaccination verification systems and apps. While some countries, such as South Korea, employed the latest technical solutions such as blockchain technology in the verification of the COVID-19 vaccination certificates, many other countries were not doing so or were not able to do so, though the potential in the application of emerging technologies, such as blockchain technology, has been mentioned as a way forward to protect personal privacy implemented in COVID-19 vaccine passports and contact tracing [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the specific reasons for supporting or opposing the introduction of a wrist-worn electronic device that tracks real-time location during quarantine was analysed graphically using a bar chart. Regarding the determinants of the public acceptance of tracking devices (Table 3), it can be observed that socio- where diagnosed patients were found) by dividing the data periods into three phases; before the peak of the first wave, during the peak, and after the peak [14]. The results…”
Section: Discussionmentioning
confidence: 95%
“…After the peak, people with higher education levels were more likely to adopt the apps [12]. On the other hand, low-income respondents were prone to utilize COVID-19 apps more frequently even though they tended to use COVID-19 apps late [14]. Moreover, the findings indicated that younger respondents as well as respondents with lower income and lower education levels were less likely to adopt COVID-19 apps [14].…”
Section: Overallmentioning
confidence: 91%
See 2 more Smart Citations